La muerte fetal y la muerte neonatal tienen origen multifactorial* - Huiza, Lilia (2003)
Obejetive: To identify the etiopathogenic factors associated to both fetal and neonatal deaths in Lima, Peru. Materials and methods: Retrospective study of all the cases of fetal death over 20 weeks gestation and neonatal death before 28 days of life that underwent autopsy and histopathologic study, in order to identify the cause of perinatal death. Settings: Hospital San Bartolomé in Lima, between January 1, 1996 and December 31, 2000. Results: The prevalence of fetal death was 1,68% (508/30125) and neonatal death 1,44% (434/30125). All fetal deaths and 58,8% (255/434) of the neonatal deaths underwent autopsy. Among 508 fetal deaths, 92 (18%) presented signs of autolysis that did not allow appropiate identification of the etiopathogenic process. Fetal death was associated to prematurity (60,5%), nutricional/vascular defect (78,1%), social privation (60,8%), congenital anomaly (14,6%) and inflammatory response (12,9%). Neonatal death was associated to prematurity (71,7%), social privation (61,1%), nutritional/vascular defect (59,6%), congenital anomaly (28,6%) and infammatory response (20,0%). Conclusions: Fetal death is a consequence of pathogenic factors that interact early with the maternal-embryo/fetus unit. Fetal/neonatal death tissue usually show histologic findings of several pathogenic factors simultaneously.